2021
DOI: 10.1016/j.annonc.2021.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab with carboplatin, paclitaxel, and bevacizumab for first-line treatment of advanced nonsquamous non-small-cell lung cancer

Abstract: Background: This international, randomized, double-blind phase III study (ONO-4538-52/TASUKI-52) evaluated nivolumab with bevacizumab and cytotoxic chemotherapy as first-line treatment for nonsquamous non-small-cell lung cancer (NSCLC). Patients and methods: Between June 2017 and July 2019, this study enrolled treatment-naïve patients with stage IIIB/ IV or recurrent nonsquamous NSCLC without sensitizing EGFR, ALK, or ROS1 alterations. They were randomly assigned in a 1 : 1 ratio to receive nivolumab or placeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
107
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(110 citation statements)
references
References 35 publications
2
107
1
Order By: Relevance
“…The patient in case 1 achieved a significant remission, although both PD-L1 and PD-1 were negative, which is consistent with the results of some studies [ 19 ]. The reason may include conflicting results between different detection antibodies, heterogeneity in PD-L1 expression within and across tumor sites, and temporally dynamic PD-L1 expression [ 20 ].…”
Section: Discussionsupporting
confidence: 91%
“…The patient in case 1 achieved a significant remission, although both PD-L1 and PD-1 were negative, which is consistent with the results of some studies [ 19 ]. The reason may include conflicting results between different detection antibodies, heterogeneity in PD-L1 expression within and across tumor sites, and temporally dynamic PD-L1 expression [ 20 ].…”
Section: Discussionsupporting
confidence: 91%
“…For non-squamous NSCLC, four phase III trials showed a clinical benefit of PD-1/PD-L1 inhibitors in combination with platinum-based chemotherapy. Carboplatin (CBDCA)/Pemetrexed (PEM)/Pembrolizumab, CBDCA or CDDP/PEM/atezolizumab, CBDCA/nanoparticle albumin bound-Paclitaxel (nabPTX)/atezolizumab, CBDCA/PTX/bevacizumab (BEV)/atezolizumab and CBDCA/PTX/BEV/nivolumab are now standard treatment options for non-squamous NSCLC in a front-line setting [ 6 , 7 , 8 , 9 , 10 ]. With respect to squamous NSCLC, phase III trials comparing CBDCA/PTX or nabPTX/pembrolizumab to CBDCA/PTX or nabPTX showed a survival benefit [ 33 ].…”
Section: Current Ici Therapeutic Strategies In Nsclcmentioning
confidence: 99%
“…However, the clinical trials of ICIs combined with chemotherapy have reshaped NSCLC therapy and to yield a variety of first-line treatment options for patients. The growing use of ICIs has dramatically improved patient outcome and the overall three-year survival rate of stage IV NSCLC has reached 40–50% [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. The therapeutic effects of ICIs in these clinical trials have been associated with PD-L1 tumor proportion scores (TPS) or tumor mutational burden (TMB).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Randomized trials have revealed that anti-PD-1 mAbs (pembrolizumab and nivolumab) and anti-PD-L1 mAb (atezolizumab) provide additional benefits in both overall survival (OS) and progression-free survival (PFS) for patients with previously treated advanced NSCLC, compared with chemotherapy [ 7 , 8 , 9 , 10 , 11 ]. ICIs are also recommended as a first-line treatment for advanced or metastatic NSCLC, either as monotherapy or in combination with chemotherapy or other targeted agents, based on histology, genetic alterations, and level of PD-L1 expression [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%